The Role of Return on Equity in Moderating the Effect of Current Ratio on Debt-to-Equity Ratio in Pharmaceutical and Healthcare Companies - Zulkifli Zulkifli (IJBLE Scientific Publications Community Inc., 2026)
The pharmaceutical and healthcare industry in Indonesia is facing increasing demand for healthcare services, the need for digital transformation, and high dependence on imported pharmaceutical raw materials, all of which increase corporate financing requirements. This study aims to analyse the effects of liquidity and profitability on capital structure and to examine the role of profitability as a moderating variable in the relationship between liquidity and capital structure among Pharmaceutical and Healthcare Resources companies in Indonesia. This research employed a quantitative approach with a causal research design. The study population consisted of 13 companies, of which 10 were selected using purposive sampling during the 2021-2024 period. Data were analysed using panel data regression with the Moderated Regression Analysis (MRA) approach. The results indicate that the Current Ratio (CR) and Return on Equity (ROE) partially have negative and significant effects on the Debt-to-Equity Ratio (DER). Furthermore, ROE is shown to positively and significantly moderate the effect of CR on DER. These findings theoretically extend the perspective of the Pecking Order Theory and provide practical implications for corporate management in making optimal financing decisions, while also serving as a consideration for investors in making investment decisions.